Architectural shop drawing of elevation, section and part plans AST1-4 (RFA-266_Rev E) - BUCG-ABC Joint Venture (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of PDF version of drawings.